THE TRANSLATION OF POLITENESS IN SUPERNOVA: KSATRIA, PUTRI & BINTANG JATUH INTO SUPERNOVA: THE KNIGHT, THE PRINCESS AND ÂTHE FALLING STAR - Ni Putu Santi Ashari Rahayu; I Gusti Ayu Gde Sosiowati; I Nyoman Arya Wibawa (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
This study aims to find out and analyze types of politeness strategy expressed by the characters in the novel, to find out the procedures of translation applied to translate the politeness strategy applied by the characters in the novel and also to identify factors that affect the translation of politeness differences in the novel entitled Supernova: Ksatria, Putri & Bintang Jatuh translated into English. The data of this study was taken from a novel entitled Supernova: Ksatria, Putri & Bintang Jatuh and its translation into English. This study is limited into only analyzing the politeness strategy expressed by the characters in the novel and also analyzing translation procedures applied in translating politeness in the source language to the target language. This study used a qualitative method means the data are collected by observation and note taking process. The theories applied in this study such as from Brown & Levinson (1978) to analyze the politeness strategy, the procedures of translation theory proposed by Vinay and Dalbernet (in Hatim and Munday (2004), and to analyze factors that affect the translation of politeness in the novel, theory based on the ideas of the possibility in translation by Cohen (1985) which is also related to Rand (1966) philosophy of objectivism, objective reality & conceptual equivalence, and anthropological linguistics by Foley (1997) are applied. The result of this study showed that the type of politeness which mostly applied in the dialogue is positive politeness, the politeness strategies in the dialogue of the novel presented in oblique translation, and the politeness differences applied in the novel (Bahasa Indonesia and English version) held a very important role in forming and delivering the right messages that wanted to convey by the author to target language. The translator who also played an important role in bridging the message also consider context, and more importantly culture in which belong to the expected target readers.